To the experience in the use of tests for current control of knowledge on historical geology in MGRI - E. S. Gaponenko; L. V. Novgorodova; E. S. Lekaj; R. U. Eremenko; V. N. Komarov; A. O. Andruhovych (Известия высших учебных заведений: Геология и разведка)
The possibilities of using test tasks of various forms for the current control of the objective assessment of students knowledge of historical geology have been clarified. Brief information about the essence of pedagogical control and tests has been given. The value of control maps for the analysis and statistical processing of test results has been considered. The effectiveness of the test verification system for the organization of self-control over the course of assimilation and consolidation of the acquired knowledge, as well as the implementation of self-management training activities of students, has been proved. It has been concluded that the educational material that affects the history of the Earth in the Precambrian is the most difficult (10,0% of the correct answers), as well as the various aspects of the evolution of the organic world (10,1%), and alsothe information about minerals (11,5%). Students showed the best knowledge in the field of stratigraphic division of the studied intervals of geological history of the Earth (50,4%), features of the Paleozoic stage (42,4%) and various historical aspects (37,3%). It has been established that the maximal difficulties, regardless of the content, cause the tasks requiring systematic knowledge for compliance (9,4%). A small positive dynamics of students performance indicators has been revealed in the study of the material relating to different ages and different types of tectonic structures, as well as in the work with tests to establish compliance. It has been proved that the test control system makes it possible to make more systematic and effective conduct of classes, organize a self-control over the course for mastering individual topics and adjust the lecture material to improve the efficiency of training. Data on the results of the test control of educational work should be fully used for timely adjustment of educational trajectories of students at all stages of training in historical geology. They will be necessary for the development of initiatives in mastering the future profession, creative abilities, the ability to plan and predict the results of their independent actions and to solve non-standard tasks.